Evaluation of the hepatotoxicity of Psoralea corylifolia L. based on a zebrafish model - Gao, Shu-Yan; Zhao, Jing-Cheng; Xia, Qing; Sun, Chen; Aili, Maimaiti; Talifu, Ainiwaer; Huo, Shi-Xia; Zhang, Yun; Li, Zhi-Jian (Frontiers in Pharmacology, 2024)
Objective:Psoralea corylifolia L. (FP) has received increasing attention due to its potential hepatotoxicity. Methods: In this study, zebrafish were treated with different concentrations of an aqueous extract of FP (AEFP; 40, 50, or 60 μg/mL), and the hepatotoxic effects of tonicity were determined by the mortality rate, liver morphology, fluorescence area and intensity of the liver, biochemical indices, and pathological tissue staining. The mRNA expression of target genes in the bile acid metabolic signaling pathway and lipid metabolic pathway was detected by qPCR, and the mechanism of toxicity was initially investigated. AEFP (50 μg/mL) was administered in combination with FXR or a peroxisome proliferator-activated receptor α (PPARα) agonist/inhibitor to further define the target of toxicity. Results: Experiments on toxic effects showed that, compared with no treatment, AEFP administration resulted in liver atrophy, a smaller fluorescence area in the liver, and a lower fluorescence intensity (p < 0.05); alanine transaminase (ALT), aspartate transaminase (AST), and γ-GT levels were significantly elevated in zebrafish (p < 0.01), and TBA, TBIL, total cholesterol (TC), TG, low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) levels were elevated to different degrees (p < 0.05); and increased lipid droplets in the liver appeared as fatty deposits. Molecular biological validation revealed that AEFP inhibited the expression of the FXR gene, causing an increase in the expression of the downstream genes SHP, CYP7A1, CYP8B1, BSEP, MRP2, NTCP, peroxisome proliferator-activated receptor γ (PPARγ), ME-1, SCD-1, lipoprotein lipase (LPL), CPT-1, and CPT-2 and a decrease in the expression of PPARα (p < 0.05). Conclusion: This study demonstrated that tonic acid extracts are hepatotoxic to zebrafish through the inhibition of FXR and PPARα expression, thereby causing bile acid and lipid metabolism disorders.